On an Unknown Mid-14th Century Bulgarian Manuscript Containing the Catena to the Psalter - Николова, Светлина (Studia Ceranea, 2016)
The texts of the oldest Slavonic translation of the Psalter are among the most thoroughly studied texts of Cyril‘s and Methodius‘ translations in all their different forms. The history of these texts has already been clarified in many respects. However, we observe the fact that research and publications are usually based on a very narrow range of manuscripts, the largest part of which were discovered and put into scientific circulation already in the 19th century. Very rarely, new data appear on the manuscript tradition until the 14th century, the studies do not even use manuscripts known for a long time. This observation applies mostly to the commented texts. This article introduces for the first time into scientific circulation the text of a so far unknown catena to the Psalter, found in a Bulgarian manuscript from the 14th century, and makes a first attempt to determine its place and importance in the development of the Psalter text among the Slavs.